NLR-Dependent Regulation of Inflammation in Multiple Sclerosis - Gharagozloo, Marjan; Gris, Katsiaryna V.; Mahvelati, Tara; Amrani, Abdelaziz; Lukens, John R.; Gris, Denis (Frontiers in Immunology, 2018)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) associated with inappropriate activation of lymphocytes, hyperinflammatory responses, demyelination, and neuronal damage. In the last decade, a number of biological immunomodulators have been developed that suppress the peripheral immune responses and slow down the progression of the disease. However, once the inflammation of the CNS has commenced, it can cause serious permanent neuronal damage. Therefore, there is a need for developing novel therapeutic approaches that control and regulate inflammatory responses within the CNS. NOD-like receptors (NLRs) are intracellular regulators of inflammation expressed by many cell types within the CNS. They redirect multiple signaling pathways initiated by pathogens and molecules released by injured tissues. NLR family members include positive regulators of inflammation such as NLRP3 and NLRC4 and anti-inflammatory NLRs such as NLRX1 and NLRP12. They exert immunomodulatory effect on the level of peripheral immune responses including antigen recognition and lymphocyte activation and differentiation. Also, NLRs regulate tissue inflammatory responses. Understanding the molecular mechanisms that are placed at the crossroad of innate and adaptive immune responses such as NLR-dependent pathways could lead to the discovery of new therapeutic targets. In this review, we provide a short summary of the role of NLRs in the pathogenesis of MS. We also summarize how anti-inflammatory NLRs regulate the immune response within the CNS. Finally, we speculate the therapeutic potential of targeting NLRs in MS.